2016
DOI: 10.3945/ajcn.115.113456
|View full text |Cite
|
Sign up to set email alerts
|

The motilin receptor agonist erythromycin stimulates hunger and food intake through a cholinergic pathway

Abstract: Background: Motilin-induced phase III contractions have been identified as a hunger signal. These phase III contractions occur as part of the migrating motor complex (MMC), a contractility pattern of the gastrointestinal tract during fasting. The mechanism involved in this association between subjective hunger feelings and gastrointestinal motility during the MMC is largely unknown, however, as is its ability to stimulate food intake. Objectives: We sought to 1) investigate the occurrence of hunger peaks and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
34
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 32 publications
(40 citation statements)
references
References 42 publications
3
34
0
Order By: Relevance
“…In the present study, we replicated the hunger-inducing effect of the motilin agonist erythromycin found in previous studies in healthy female volunteers by our group 7 , 8 . Further, we demonstrated for the first time that this leads to increased hedonic food intake 50 minutes after the start of the infusion (although it should be noted that only a non-significant trend was found, which may be due to the late administration of the test relative to infusion, see below).…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…In the present study, we replicated the hunger-inducing effect of the motilin agonist erythromycin found in previous studies in healthy female volunteers by our group 7 , 8 . Further, we demonstrated for the first time that this leads to increased hedonic food intake 50 minutes after the start of the infusion (although it should be noted that only a non-significant trend was found, which may be due to the late administration of the test relative to infusion, see below).…”
Section: Discussionsupporting
confidence: 91%
“…Regarding the stimulatory effect of a low dose of erythromycin on hunger and prospective food consumption ratings, we confirmed previous work by our group 7 , 8 . In line with these effects on subjective ratings, there was a trend towards more hedonic food intake after erythromycin infusion compared to placebo, with a small effect size (Cohen’s d : 0.44).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Endogenous motilin 52 plasma levels, but not ghrelin, fluctuate in synchrony with antral contractility of the MMC, to 53 reach a peak just before the occurrence of a gastric phase III (16,17,19). We recently showed 54 that motilin-induced gastric phase III contractions of the MMC signal hunger in healthy 55 volunteers and that motilin plasma levels were closely associated with interdigestive hunger 56 ratings (20,21). In 1916, Carlson (22) reported an inhibitory effect of intragastrically 57 administered bitter compounds on both fasting gastric contractility and hunger sensations, 58 but the underlying mechanism was not elucidated.…”
mentioning
confidence: 99%